2021
DOI: 10.1186/s13052-021-01029-0
|View full text |Cite
|
Sign up to set email alerts
|

How to recognize and manage psychosomatic pain in the pediatric emergency department

Abstract: Aim Children and adolescents affected by somatization and somatic symptom disorder commonly refer to emergency services. Due to the absence of specific guidelines for the emergency setting and to a possible lack of knowledge, these patients are at risk of being unrecognized and mismanaged. This study aims at proposing a clinical practice to approach and manage these patients and their families in the emergency setting. Methods This manuscript deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The immediate nature of the ED clinician’s invitation may explain the high follow-through we observed. Consistent with our findings, a direct and seamless approach to somatization intervention is supported by existing clinical recommendation and work done in primary care settings ( Abbass, 2005 ; Abbass et al, 2009 ; Cozzi et al, 2021 ). Our findings support the potential for cross-disciplinary collaboration between emergency and consultation psychiatry teams, in somatization identification and psychoeducation.…”
Section: Discussionsupporting
confidence: 90%
“…The immediate nature of the ED clinician’s invitation may explain the high follow-through we observed. Consistent with our findings, a direct and seamless approach to somatization intervention is supported by existing clinical recommendation and work done in primary care settings ( Abbass, 2005 ; Abbass et al, 2009 ; Cozzi et al, 2021 ). Our findings support the potential for cross-disciplinary collaboration between emergency and consultation psychiatry teams, in somatization identification and psychoeducation.…”
Section: Discussionsupporting
confidence: 90%
“…Pain symptoms may also reflect underlying structural abnormalities in the cerebellum. Pain is one of the most common symptoms among patients with SSD ( Kurlansik and Maffei, 2016 ; Cozzi et al, 2021 ; Nazzal et al, 2021 ). In this study, the most common complaints among patients with SSD were headache, fatigue, and dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…These included somatic symptom disorders, anxiety disorders and depression. 7 The specific clinical features reported by adolescents categorised as affected by long COVID seem to mirror the highly suggestive symptoms for somatic symptoms and mental health disorders in general. They have also been more prevalent in adolescents, patients with long‐lasting physical symptoms, severe fatigue and chronic pain and those who are unable to attend school because they feel sick, subjects socially isolated who and have a poor quality of life.…”
mentioning
confidence: 87%
“… 7 As mentioned, adolescents with long COVID are likely to benefit from the same effective multidisciplinary therapeutic approaches, aimed to regain functioning, for patients with somatic symptom disorder. 7 Clinical practice experience and study data indicate that patients with features that suggested somatic symptom disorders frequently received other diagnostic labels, based on the types of symptoms and the clinics they were referred to. These may include chronic fatigue syndrome, fibromyalgia and chronic Lyme disease.…”
mentioning
confidence: 99%